Searching a political unanimity. The campaign of Juan Manuel de Rosas against the North Coalition in the light of the ‘Manuel Oribe’s file’, 1838-1842 (Palimpsesto, 2018)
This work has as a main goal making an approach to the military campaign that Juan Manuel de Rosas,chief of the Argentinian Confederation, and Manuel Oribe, as general in chief of the Confederation´sVanguard Army, took ahead against the ‘North Coalition’. The documents that give strength to thisresearch is the “Manuel Oribe´s file” (unpublished), placed in the Historical Provincial Museum ofRosario, Argentina. In this article we will analyze relationships between war and politics, as well as thechanges happened in the scenario through which military development moved in this critical conjuncture.
Keywords: Juan Manuel de Rosas; Manuel Oribe; North Coalition; Argentinian Confederation; War